Plant Defense Mechanisms against Polycyclic Aromatic Hydrocarbon Contamination: Insights into the Role of Extracellular Vesicles - Muttiah Barathan; Sook Luan Ng; Yogeswaran Lokanathan; Min Hwei Ng; Jia Xian Law (Toxics)
Polycyclic aromatic hydrocarbons (PAHs) are persistent organic pollutants that pose significant environmental and health risks. These compounds originate from both natural phenomena, such as volcanic activity and wildfires, and anthropogenic sources, including vehicular emissions, industrial processes, and fossil fuel combustion. Their classification as carcinogenic, mutagenic, and teratogenic substances link them to various cancers and health disorders. PAHs are categorized into low-molecular-weight (LMW) and high-molecular-weight (HMW) groups, with HMW PAHs exhibiting greater resistance to degradation and a tendency to accumulate in sediments and biological tissues. Soil serves as a primary reservoir for PAHs, particularly in areas of high emissions, creating substantial risks through ingestion, dermal contact, and inhalation. Coastal and aquatic ecosystems are especially vulnerable due to concentrated human activities, with PAH persistence disrupting microbial communities, inhibiting plant growth, and altering ecosystem functions, potentially leading to biodiversity loss. In plants, PAH contamination manifests as a form of abiotic stress, inducing oxidative stress, cellular damage, and growth inhibition. Plants respond by activating antioxidant defenses and stress-related pathways. A notable aspect of plant defense mechanisms involves plant-derived extracellular vesicles (PDEVs), which are membrane-bound nanoparticles released by plant cells. These PDEVs play a crucial role in enhancing plant resistance to PAHs by facilitating intercellular communication and coordinating defense responses. The interaction between PAHs and PDEVs, while not fully elucidated, suggests a complex interplay of cellular defense mechanisms. PDEVs may contribute to PAH detoxification through pollutant sequestration or by delivering enzymes capable of PAH degradation. Studying PDEVs provides valuable insights into plant stress resilience mechanisms and offers potential new strategies for mitigating PAH-induced stress in plants and ecosystems.